1990
DOI: 10.1007/bf00314665
|View full text |Cite
|
Sign up to set email alerts
|

Cause of death among patients with Parkinson's disease: a rare mortality due to cerebral haemorrhage

Abstract: Causes of death, with special reference to cerebral haemorrhage, among 240 patients with pathologically verified Parkinson's disease were investigated using the Annuals of the Pathological Autopsy Cases in Japan from 1981 to 1985. The leading causes of death were pneumonia and bronchitis (44.1%), malignant neoplasms (11.6%), heart diseases (4.1%), cerebral infarction (3.7%) and septicaemia (3.3%). Cerebral haemorrhage was the 11th most frequent cause of death, accounting for only 0.8% of deaths among the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…Consequently, complications due to hyperten sion may be rare in Parkinson's disease. In our study of causes of death among pathologically verified patients with Parkinson's disease from 1981 to 1985 in Japan, cerebral hemorrhage was a rare cause of death, even though it was one of the leading causes among the gen eral population [27],…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, complications due to hyperten sion may be rare in Parkinson's disease. In our study of causes of death among pathologically verified patients with Parkinson's disease from 1981 to 1985 in Japan, cerebral hemorrhage was a rare cause of death, even though it was one of the leading causes among the gen eral population [27],…”
Section: Discussionmentioning
confidence: 99%
“…poor nutritional status), have distressing levels of poor comfort, including symptoms of illness, which they are usually not able to communicate [18]. Hence the very high reported levels of pneumonia and febrile conditions [18,19]. This cascade is illustrated in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In all three cases the actual event precipitating death is usually an infection, neoplasm or cardiovascular event [18,19]. The most clinically relevant observations regarding these diseases is that toward the end of life persons with these degenerative conditions tend to become bed ridden (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…While some studies have found that the incidence of stroke was significantly lower in PD patients than controls [12, 13], others have found no significant difference [14]. Similarly, the relationship between hypertension and PD is not clear.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the relationship between hypertension and PD is not clear. PD patients are less likely to suffer from clinical hypertension [15, 16]and many anti-parkinsonian drugs initiate hypotensive effects due to a reduction in noradrenalin levels in the parkinsonian brain [13]. Nonetheless, there is no direct evidence to suggest that hypertension is protective with respect to PD.…”
Section: Discussionmentioning
confidence: 99%